SOSIALISASI STRATEGI MANAJEMEN SEKOLAH DALAM MENANGANI BULLYING DAN KEKERASAN DI LINGKUNGAN SEKOLAH SMAN 1 XIII KOTO KAMPAR - Irawan, Dika; Primadayani, Syurti; Azmi, Fauzan; Hidayat, Novit; Nurhayati, Nurhayati (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
The socialization of school management strategies in handling bullying and violence at SMA N 1 XIII Koto Kampar is an important step in creating a safe, comfortable, and conducive learning environment. Based on the results of the study, socialization has been carried out through various approaches, such as homeroom teacher meetings, student coaching, counseling from Az Zuhra Institute lecturers, and the use of school information media. The school management strategy involves the prevention, handling, and evaluation of bullying and violence cases with a collaborative approach between the principal, teachers, and students. This shows that socialization needs to be carried out more intensively and structured so that the designed strategy can be implemented optimally. At the end of the community service activity, we held a group photo session and presented a certificate of appreciation to the principal who had helped run this community service activity. We also held a friendly gathering with the principal to discuss how to continue this program. According to the principal, we saw the enthusiasm of the students in listening to the presentation. Furthermore, we from the community service team also hoped that students understood the importance of preventing bullying starting from themselves. We, the community service team, welcomed this warmly and, God willing, we will follow up on the principal's good wishes, until finally, precisely at 12:00 noon, the community service event was completed and ran smoothly